2018
DOI: 10.3390/cells7090116
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Constituents from the Sclerotia of Poria cocos against Human Lung Adenocarcinoma Cells by Inducing Mitochondrial Apoptosis

Abstract: Previous studies have revealed the antitumor potential of Poria cocos Wolf against a broad spectrum of cancers. However, the biological activity of P. cocos against lung cancer, which is known as the leading cause of cancer mortality worldwide, and its underlying chemical and molecular basis, remain to be investigated. We aimed to evaluate the in vitro cytotoxicity of P. cocos toward human lung adenocarcinoma cells with different p53 statuses, to identify the bioactive constituents of P. cocos, and explicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…walteri stems and stem barks collected from Jeju Island, Korea were extracted with 80% aqueous MeOH under reux, and then evaporated under a vacuum to obtain a MeOH crude extract, which was subsequently solvent-fractionated with hexane, CHCl 3 , and n-BuOH, yielding soluble fractions of each solvent. Signicant spots were detected in the hexane-soluble fraction aer TLC analysis, and the hexane-soluble fraction was subjected to repeated column chromatography and HPLC purication, which resulted in the isolation of 15 compounds, including seven triterpenoids (1-7), ve steroids (8)(9)(10)(11)(12), two diterpene analogs (13 and 14), and one phenolic compound (15). Based on a comparison of their spectroscopic (including 1 H and 13 C NMR) and physical data with previously reported values and LC/MS analyses, the chemical structures of all the isolates were determined and identied as: leucophyllone (1), 11 3-O-acetylbetulin (2), 20 betulinic acid methyl ester (3), 21 lupenone (4), 22 methyl 3-O-acetylbetulinate (5), 23 lupeol (6), 24 betulinic acid (7), 25 6b-hydroxysitostenone (8), 26 sitostenone (9), 27 5astigmast-3,6-dione (10), 28 3b-sitostanol (11), 29 6a-hydroxy-bsitostenone (12), 30 norphytan (13), 31 phytone 14, 32 and benzyl salicylate (15) 33 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…walteri stems and stem barks collected from Jeju Island, Korea were extracted with 80% aqueous MeOH under reux, and then evaporated under a vacuum to obtain a MeOH crude extract, which was subsequently solvent-fractionated with hexane, CHCl 3 , and n-BuOH, yielding soluble fractions of each solvent. Signicant spots were detected in the hexane-soluble fraction aer TLC analysis, and the hexane-soluble fraction was subjected to repeated column chromatography and HPLC purication, which resulted in the isolation of 15 compounds, including seven triterpenoids (1-7), ve steroids (8)(9)(10)(11)(12), two diterpene analogs (13 and 14), and one phenolic compound (15). Based on a comparison of their spectroscopic (including 1 H and 13 C NMR) and physical data with previously reported values and LC/MS analyses, the chemical structures of all the isolates were determined and identied as: leucophyllone (1), 11 3-O-acetylbetulin (2), 20 betulinic acid methyl ester (3), 21 lupenone (4), 22 methyl 3-O-acetylbetulinate (5), 23 lupeol (6), 24 betulinic acid (7), 25 6b-hydroxysitostenone (8), 26 sitostenone (9), 27 5astigmast-3,6-dione (10), 28 3b-sitostanol (11), 29 6a-hydroxy-bsitostenone (12), 30 norphytan (13), 31 phytone 14, 32 and benzyl salicylate (15) 33 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our continued quest to discover biologically novel natural products from a variety of Korean natural resources, [13][14][15][16][17] our group has explored the potential bioactive constituents of C. walteri. 11,18,19 Our previous studies reported that the MeOH extract of the stems and stem barks of C. walteri are signicantly cytotoxic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the continuing research into bioactive compounds from Korean medicinal plant sources [13][14][15][16][17], the MeOH extract of the aerial portion of L. cuneata was found to exhibit cytotoxic effects on human ovarian carcinoma cells [5]. In our recent study, bioassay-guided fractionation of the MeOH extract using repeated chromatography resulted in the isolation of (−)-9 -O-(α-l-rhamnopyranosyl)lyoniresinol, which inhibited the proliferation of A2780 human ovarian carcinoma cells through the induction of apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our continuing projects to explore biologically active, unique natural products from diverse natural sources [18][19][20][21][22], we recently took note of Ulmus davidiana var. japonica, the root barks of which have been used as a Korean traditional medicine for various therapeutic purposes including gastroenteric disorders and inflammatory disorders [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%